Molecular characterization, expression and function analysis of Epinephelus coioides PKC-ɑ response to Singapore grouper iridovirus (SGIV) infection. (May 2023) - Cai, Yi-Jie; He, Jia-Yang; Yang, Xin-Yue; Huang, Wei; Fu, Xue-Mei; Guo, Shi-Qing; Yang, Jie-Jia; Dong, Jun-De; Zeng, Hai-Tian; Wu, Yan-Jun; Qin, Zhou; Qin, Qi-Wei; et al.
Abstract: Protein kinase C (PKC) constitutes the main signal transduction pathway, and participates in the signal pathway of cell proliferation and movement in mammals. In this study, PKC-ɑ was obtained from Epinephelus coioides, an important marine fish cultivated in the coastal areas of southern China and Southeast Asia. The full length cDNA of PKC-ɑ was 3362 bp in length containing a 23 bp 5′UTR, a 1719 bp 3′UTR, and a 1620 bp open reading frame encoding 539 amino acids. It contains three conservative domains including protein kinase C conserved region 2 (C2), Serine/Threonine protein kinases, catalytic domain (S_TKc) and ser/thr-type protein kinases (S_TK_X). Its mRNA can be detected in all 11 tissues examined of E. coioides, and the expression was significantly upregulated response to Singapore grouper iridovirus (SGIV) infection, one of the important pathogens of marine fish. Upregulated E. coioides PKC-ɑ significantly inhibited the activation of nuclear factor kappa-B (NF-κB) and activator protein-1 (AP-1), and SGIV-induced cell apoptosis. The results indicated that the PKC-ɑ may play an important role in pathogenic stimulation. Highlights: Protein kinase C-ɑ (PKC-ɑ) from Epinephelus coioides was identified and characterized. The expression of E. coioides Hsp27 was up-regulated during SGIV infection. Overexpression E. coioides Hsp27 inhibited SGIV-induced cell apoptosis.